Phenotypic characters and identification CYPs (Cyclophilin) gene in Cucumis melo L. cv. Gama Melon Parfum - WIKO ARIF WIBOWO; SIGIT DWI MARYANTO; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wibowo WA, Maryanto SD, Daryono BS. 2021. Phenotypic characters and identification CYPs (Cyclophilin) gene in Cucumis melo L. cv. Gama Melon Parfum. Biodiversitas 22: 3007-3014. Cucumis melo L. cv. Gama Melon Parfum is a new cultivar with a very strong fragrance as its main character. As a new cultivar with unique characters, it is necessary to characterize phenotype and molecular related to the fragrant aroma. The research aimed to study the phenotypic of the fruit of C. melo cv. Gama Melon Parfum (F3) and to identify the CYPs gene as one of the genes that act in encoding volatile compounds. Analysis of qualitative characters was based on International Plant Genetic Resources Institute (IPGRI) and Plant Variety Protection (PVP), phenotypic characters in melons observed by abiding the Rules for Registration of Varieties from the Indonesian Minister of Agriculture Decree No. 700/Kpts/OT.320/D/12/2011, while analysis of quantitative characters was using the ANOVA methods and software PKBT-STAT-2. The methods of molecular characterization included RNA isolation, cDNA synthesis used Reverse Transcriptase-PCR, amplification of DNA target used PCR, visualization of DNA target used electrophoresis, and DNA sequencing. Analysis of the in silico approach was carried out on the CuGenDB Melon database. Analysis of protein sequences and classification was obtained from InterPro. Phylogeny analysis using MEGA-X Software. The results were 18 qualitative characters and 11 quantitative characters were stable and uniform, whereas the molecular characterization of the genes was predicted Cyclophilin with peptidylprolyl isomerase (PPIase) activity and located in chromosome 1 (17059021-17058899).